Wastewater Characterization Survey, Thule Air Base, Greenland - McCoy, Richard P. (1993)
A wastewater characterization survey was conducted at Thule AB, Greenland,from 6-22 July 1992 by personnel from the Water Quality Function of Armstrong Laboratory. Extensive sampling of the outfall feeding into North Star Bay and industrial sites within the base cantonment area was performed. Low levels of organic contamination were found in the wastewater. In addition, metals and other pollutants were found in concentrations typical of domestic wastewater, indicating little contamination from industrial activities. Daily flow averaged approximately 100,000 gallons per day (375 cubic meters per day). The average chemical oxygen demand was found to be 130 milligrams per liter. The biochemical oxygen demand (BOD), though not determined experimentally during this survey, can be expected to fall within the range of 75-100 mg/l.